Impulse oscillometry and nitrogen washout test in the assessment of small airway dysfunction in asthma: Correlation with quantitative computed tomography. (4th March 2019) - Fuso, Leonello; Macis, Giuseppe; Condoluci, Carola; Sbarra, Martina; Contu, Chiara; Conte, Emanuele G.; Angeletti, Giulia; Montuschi, Paolo
ABSTRACT: Objective . Small airway dysfunction (SAD) and airway remodeling influence the disease control and progression in asthma. We investigated whether impulse oscillometry (IOS) and single breath nitrogen washout (SBN2 W) could be reliable tests in evaluating SAD and airway remodeling by correlating their data with radiological parameters derived from quantitative chest multidetector computed tomography (MDCT) imaging. Methods . Lung function tests were performed before and after bronchodilator. The MDCT lung scans were acquired at full inspiration and expiration using a portable spirometer to control the respiratory manoeuvres. Symptom control was assessed using the Asthma Control Test (ACT) questionnaire. Results . Twenty six patients were enrolled. The bronchial lumen area (LA) measured with MDCT lung scan, correlated inversely with airway resistance (Raw, p < 0.001) and with total and large airway oscillometric resistance (R5, p = 0.002 and R20, p = 0.006, respectively). However these two last correlations became non-significant after Bonferroni correction for multiple comparisons. The radiological quantification of air trapping correlated with Raw ( p < 0.001), residual volume (RV, p < 0.001), and the slope of phase III of SBN2 W (DeltaN2, p < 0.001) whereas the correlation with small airway oscillometric resistance (R5-20) was non-significant after Bonferroni adjustment. Finally, air trapping was significantly higher in patients with a fixed bronchial obstruction in comparison to patients with reversible obstruction. Conclusions . Plethysmographic method remains the main tool to investigate SAD and airway remodeling in asthmatic patients. The integration with the SBN2 W test proved useful to better evaluate the small airway involvement whereas IOS showed a weaker correlation with both radiological and clinical data.